Preventionof HIV/aids in a model female penitentiary in São Paulo – SP, Brazil - Strazza, Leila; Azevedo, Raymundo S.; Carvalho, Heráclito B. (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the prison cannot be considered just as a place to spare the inflationary people from their environment or only to punish them. The prisons alsohave the difficulty task of rehabilitation. Their adverse environmental conditions contribute to higher exposition risk to infectious diseases mainly HIV/aids.Objective: to evaluate positive and negative points of prevention HIV/AIDS in a São Paulo’s Model Female Prison – SP, Brazil. Methods: transversal studyfollowed by safe sex workshops performances. It was carried out among August and October, 2000. Results: 290 prisoners agreed to participate, but only 267agreed to be serologic tested: 14% HIV+ (37/267). Age: from 18 to 65 years, the most common crimes were robbery and drugs: 50% and 28, 9%, respectively,53% were single, 58% had children, 52,7% had incomplete primary school, 22% of these women were aware of having had at least one STD and they relatedtheir names, 70% of them use illicit drugs and 9% injecting drugs; 176 female prisoners participated in safe sex workshops. Descriptive data comparison amongNational and International Penitentiaries. Positive and negative points descriptions during intervention process of HIV/AIDS prevention strategies. Conclusion:the realization of AIDS prevention strategies in prisons is important and there are strong obstacles to their executions, even in a model prison – as positive point:to have permission to realize the serology and workshops; negative point: inadequate place. “If in a Model Penitentiary these educative actions find obstacles,how will it be in common prisons?”.